2018
DOI: 10.3389/fphys.2018.00274
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Landscape of Heart Rhythm in Long-Term Heart Transplant Recipients: A Way to Discern Erratic Rhythms

Abstract: It is commonly believed that higher values of heart rate variability (HRV) indices account for better organization of the network of feedback reflexes driving an organism's response to actual bodily needs. In order to evaluate this organization in heart transplant (HTX) recipients, 58 nocturnal Holter signals of 14 HTX patients were analyzed. Their dynamical properties were evaluated by short-term HRV indices and measures grounded on entropy. Estimates grouped according to the patients' clinical progress: free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…However, in certain cases (de Bruyne et al, 1999 ; Stein et al, 2008 ; Almeida-Santos et al, 2016 ; Raman et al, 2017 ; Wdowczyk et al, 2018 ) a paradoxical increase in short-term HR fluctuations was observed in contexts where reduced vagal tone would have been expected based on age and/or advanced heart disease. In the present study, we observed a U-shaped relationship between traditional short-term HRV measures and cross-sectional age (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in certain cases (de Bruyne et al, 1999 ; Stein et al, 2008 ; Almeida-Santos et al, 2016 ; Raman et al, 2017 ; Wdowczyk et al, 2018 ) a paradoxical increase in short-term HR fluctuations was observed in contexts where reduced vagal tone would have been expected based on age and/or advanced heart disease. In the present study, we observed a U-shaped relationship between traditional short-term HRV measures and cross-sectional age (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be correlated to the fact that has been found in [48] that suggests that any decrease in the fluctuations of these features are hardly to be detected in a recorded ECG data. In addition, a paradoxical increase in these fluctuations comes as a results of a reduced vagal tone that would suggest the occurrence of heart diseases [49].…”
Section: Clinical Relevancementioning
confidence: 99%
“…The stochastic features of the short term dynamics can be evaluated by [ 29 ]: entropy of transition rates self-transfer entropy …”
Section: Methodsmentioning
confidence: 99%